1989
DOI: 10.1063/1.455982
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular orientation near liquid–vapor interface of methanol: Simulational study

Abstract: Computer simulations with molecular dynamics technique were carried out to investigate properties of liquid–vapor interface of methanol for a wide temperature range of 160–350 K. The estimated surface excess thermodynamic quantities, especially surface entropy, are characteristic of strongly hydrogen-bonding liquids, but the density profile resembles that of simple fluids. Orientational structuring near the surface was also studied, and one apparent tendency, much stronger than that of water, was observed; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 11 publications
8
52
2
Order By: Relevance
“…All PE bands exhibit a similar gas–liquid shift of −1.23 eV for MeOH and −1.10 eV for EtOH, which can be explained with polarization screening by the surrounding molecules; these values are somewhat smaller than for liquid water and attributed to the larger molecular size and thus distance of the alcohol molecules. We do not see any significant contribution to the gas–liquid shift from a present (polar) orientation of the alcohol molecules at the liquid’s surface, which agrees well with an orientation almost parallel to the liquid surface found in simulations . While a reasonable description of the inelastic scattering background could be achieved with a single Gaussian in the valence region, information of electron scattering in liquid alcohols is currently lacking.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…All PE bands exhibit a similar gas–liquid shift of −1.23 eV for MeOH and −1.10 eV for EtOH, which can be explained with polarization screening by the surrounding molecules; these values are somewhat smaller than for liquid water and attributed to the larger molecular size and thus distance of the alcohol molecules. We do not see any significant contribution to the gas–liquid shift from a present (polar) orientation of the alcohol molecules at the liquid’s surface, which agrees well with an orientation almost parallel to the liquid surface found in simulations . While a reasonable description of the inelastic scattering background could be achieved with a single Gaussian in the valence region, information of electron scattering in liquid alcohols is currently lacking.…”
Section: Discussionsupporting
confidence: 86%
“…No distinct dependence on the specific PE band was found, except the splitting caused by H-bonding for MeOH and strong overlapping bands of a−e for EtOH. Previously, MeOH has been found to show a strong molecular ordering at the liquid surface, with the CH 3 pointing out of the liquid surface; 60,61 however, its permanent dipole moment is aligned parallel to the liquid surface and the resulting electrostatic surface potential is only on the order of −0.03 V. 59 Therefore, the influence of surface dipole can be neglected. Orientation with the alkyl chain pointing away from the liquid surface has also been observed for higher order alcohols.…”
Section: The Journal Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical meaning of this discrete solvent effect has been matter of considerable debate in the classical simulation literature over the last two decades, in the context of ionic solvation free energies 22,44,45,[112][113][114][115][116][117][118][119][120][121] as well as in the context of surface potential calculations. 22,[122][123][124][125][126][127][128][129][130][131][132][133][134][135][136] The authors believe that this debate and its conclusions are appropriately summarized in Ref. 22 (see also Ref.…”
Section: Discussionmentioning
confidence: 99%
“…methanol by MD simulations, and it was reported that methanol molecules in the interface have a tendency to project their methyl groups to the vapor phase. 15,29 We shall examine the molecular orientational distribution in the virtual vacuum evaporation states. According to Refs.…”
Section: ͑32͒mentioning
confidence: 99%